A Influência do Conselho Municipal de Proteção Ambiental de Pelotas no Processo de Elaboração de Políticas Públicas Ambientais Municipais no Período dentre Abril de 2008 e Abril de 2011 - Wienke, Felipe Franz (2011)
The management councils are deliberative arenas for the preparation and monitoring of public policies. In the environmental zone, the municipal councils for the environment is getting more important, especially in municipalities with responsibility for environmental licensing. The City Council Environmental Protection of Pelotas - COMPAM - collegiate parity with the participation of representatives from governmentand and civil society, is the organism higher for the establishment of environmental policy in Pelotas. This study aims to examine the relationship between the COMPAM and the municipal government by examining the influence of the collegiate on environmental policies effected by the municipality. To this end, the work is organized into four chapters. In the first, we analyze the deliberative democratic theories, the emergence and consolidation of management councils and the evolution, in the Brazilian scenario, of the environmental policies. Later, it presented the City Council Environmental Protection of Pelotas, being analyzed its regimental structure, composition, and the deliberations recorded in minutes. Then, with the research about the environmental actions by the municipal government, is investigated the influence of the COMPAM on executive decisions. Finally, through interviews with the conselors are identified potential conflicting aspects in the relationship between the COMPAM and the municipality. The conclusions of the study show that there is an obstruction in the dialogue of the COMPAM with the municipal council, which is caused both by the attitude of the collegiate such as the municipal government